The art of Ayacucho altarpieces: Religiosity, history and emerging cultural practice - Ulfe, María Eugenia (2004)
This article deals with how a religious object became popular (in the sense of "popular art" or folklore) and how it became a vehicle for opinion and modernity that is multiform and therefore diversifies the themes to be represented and their meanings. I begin by narrating an event that I witnessed in August 2001.